Eliminación del incentivo económico de las acciones populares: “constitucional pero inconveniente” (2016)
The document attempts to answer the question : Have citizens been unmotivated to carry out popular actions, by the repeal of the economic incentive given to those who achieved a favorable judgment, referred in the Law 472 of 1998? Through the analysis of legal history that gave rise to the popular action, the current situation in comparative law, as well as the jurisprudential precedent of the Constitutional Court that supported the repeal design. We conclude that citizens may have lost interest in participating as popular actors, not have the economic stimulus motivated before his performance, so once again would become a constitutional norm in inconvenience. The document provides a review of some categories such as freedom of legislative configuration, the principles of solidarity and equality within the framework of a social state of law where it is suggested that the legislator should have done a deeper study on the problems that was warned by the repealing ostensible one, and that not to debilitate the protection of the collective rights must have made unscathed the responsibility established in the article 40 of the law 472 of 1998.